An exploration of new methods to assess energy availability in the English oak (Quercus robur) - Bracewell, Kathryn Vanessa (Cranfield University, 2000)
Existing methods of measuring the capability of foods to drive ecosystem processes are reviewed and found to be inadequate; these included bomb calorimetry and plant quality assays. This thesis explores two alternative methods, one in vivo and one in vitro, based on the rate of supply of energy and compares these to plant quality measurements and calorific content. A pilot study was undertaken using cow parsley (Anthriscus sylvestris) to determine sampling regime and establish laboratory techniques for fibre content measurement. The energy availability of different parts of the English oak (Quercus robur) are compared by measuring their decomposition rates in oak woodland soil. In this form the soil is acting as an in vivo microbial digester and the rates at which weight loss occurs in the samples is converted to an energy release rate dimensioned in kW.kg-¹. This unit mass power measurement is compared to heat of combustion data derived from bomb calorimetry which is dimensioned in joules.kg-¹. Variation in unit mass heat of combustion between plant parts is small at 10% compared to the 400% (at 18 days) and 720% (at 115 days) variation in unit mass power output between plant parts as measured in the tests undertaken. Unit mass power output correlated with conventional plant quality assays of the oak. A third set of experiments has begun the development of the laboratory based measurement of energy availability under standard conditions. Each plant material was macerated in a roller mill for thirty minutes (after hammer milling where required) and subjected to a cellulose digest. A biological oxygen demand measurement was made before and after the cellulose digest. These measurements of metabolisable energy were converted to an energy supply rate by establishing a theoretical gut retention time based on the time a standard amount of cellulose takes to digest the cellulose in a unit mass of sample. The results of the in vivo and in vitro measurements were qualitatively similar but with the in vitro test energy was accessed more quickly and therefore had a higher power output rate. It is suggested that ecosystem or community energetics are dependent on energy availability rather than total energy content and that the importance of this distinction will vary between biomes.
Keywords: in vivo; in vitro; plant quality; fibre content; decomposition; woodland soil